Direct Application of Coffee Pulp Vermicompost Produced from Epigeic Earthworms and Its Residual Effect on Vegetative and Reproductive Growth of Hot Pepper (Capsicum annuum L.) - Yohannes Zergaw; Temesgen Kebede; Dargie Tsegay Berhe (The Scientific World Journal)
In areas where coffee is growing, there is a huge potential to get coffee pulp, which produces a bad odor and air and water pollution. On the other hand, the farming practice in the study area is still traditional and highly dependent on artificial fertilizers. Therefore, this study aimed to evaluate the direct and residual effects of vermicompost on the vegetative and reproductive growth of hot pepper (Capsicum annuum L.). Factorial research was conducted in a randomized complete block design, where coffee pulp, animal waste, and Eisenia fetida and Dendrobaena veneta earthworms were used to produce coffee pulp vermicompost. The first factor was three types of vermicompost: coffee pulp Eisenia fetida vermicompost (CEV), coffee pulp Dendrobaena veneta vermicompost (CDV), and a combination of coffee pulp Eisenia fetida and Dendrobaena veneta vermicompost (CEV_CDV), and the second factor was three application rates (5 t/ha, 10 t/ha, and 15 t/ha) and a control treatment with three replications. Reproductive and vegetative growth parameters (number of leaves, number of fruits, single fruit length, total biomass weight, days to 50% flowering, and yield per hectare) were collected in two consecutive cropping seasons. The collected data were analyzed using R Statistical software. The results recorded in the direct application of 15 t/ha CEV were profoundly higher (P < 0.05), followed by the combined effects of both worms with an application rate of 15 t/ha. Generally, the three-way interaction effect of a media type, the application effect, and the application rate interaction effect were highly significant (P < 0.05) for the number of leaves per plant, the number of fruits per plant, and yield per hectare. The media type and the application rate interaction effect showed a significant (P < 0.05) difference in days to 50% flowering, fruit length, and fresh biomass weight. Likewise, the combined effect of the media type and application was statistically (P < 0.01) different in biomass weight and fruit length. In addition to reducing water and air pollution, utilizing coffee pulp vermicompost enhances soil fertility and hot pepper (Capsicum annuum L.) productivity.